2022
DOI: 10.3389/fpsyg.2022.869905
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Profiles of Couples Coping With Body Image Concerns After Breast Cancer: Preliminary Results of a Cluster Analysis

Abstract: Breast cancer treatments have multiple adverse effects, including concerns about body appearance and function that are experienced by most patients. Altered body image negatively affects mental health, social, and relationship functioning. While the relationship with a partner is critical for patients’ psychological wellbeing and partners can promote positive body image, limited research has investigated individual and relational factors affecting the experience of both. This cross-sectional study aimed at (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Participants appeared extremely severe with their bodies, disqualifying them and painfully recalling their previous external look. A number of studies [4,49,50] have been conducted in the scientific literature on the connections between these factors and sexual experiences, feelings, and thoughts, as well as intimacy, complicity, and relationship with a romantic partner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants appeared extremely severe with their bodies, disqualifying them and painfully recalling their previous external look. A number of studies [4,49,50] have been conducted in the scientific literature on the connections between these factors and sexual experiences, feelings, and thoughts, as well as intimacy, complicity, and relationship with a romantic partner.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, a large proportion of patients with BC experience multiple concurrent psychological symptoms during the cancer care trajectory, such as a reduction in general quality of life, problems in relationships and sexuality, as well as negative consequences on therapeutic adherence as a result of the side effects of cancer treatments [3][4][5]. Among these, issues related to body image have long been considered important aspects of determining the quality of life of women diagnosed with BC and undergoing chemotherapy [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, additional resources must be allocated from this perspective to manage and support long-term BC survivorship. Further, it is important to identify effective interventions for the treatment of BC trauma that are aimed at responding to patients' complex health-related issues [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have shown that dyadic intervention considers the influence of social and environmental factors on physical activity and can improve the compliance and efficacy of physical activity intervention by increasing social support and strengthening social relations (Cobb et al, 2016 ; Winters-Stone et al, 2016 ; Ellis et al, 2017 ). In addition, based on previous use of the actor-partner interdependence model to explore the cancer survivors-caregiver relationship, the researchers found that the adverse effects experienced by cancer survivors can spread from the survivors to their caregivers (Saita et al, 2022 ), and caregivers of cancer survivors may experience the same or even more symptoms as survivors (Milbury et al, 2019 ). These adverse effects can in turn affect their engagement in caregiving activities.…”
Section: Introductionmentioning
confidence: 99%